Making the Switch: Alternatives to Fetal Bovine Serum for Adipose-Derived Stromal Cell Expansion - Dessels, Carla; Potgieter, Marnie; Pepper, Michael S. (Frontiers in Cell and Developmental Biology, 2016)
Adipose-derived stromal cells (ASCs) are being used extensively in clinical trials. These trials require that ASCs are prepared using good manufacturing procedures (GMPs) and are safe for use in humans. The majority of clinical trials in which ASCs are expanded make use of fetal bovine serum (FBS). While FBS is used traditionally in the research setting for in vitro expansion, it does carry the risk of xenoimmunization and zoonotic transmission when used for expanding cells destined for therapeutic purposes. In order to ensure a GMP quality product for cellular therapy, in vitro expansion of ASCs has been undertaken using xeno-free (XF), chemically-defined, and human blood-derived alternatives. These investigations usually include the criteria proposed by the International Society of Cellular Therapy (ISCT) and International Fat Applied Technology Society (IFATS). The majority of studies use these criteria to compare plastic-adherence, morphology, the immunophenotype and the trilineage differentiation of ASCs under the different medium supplemented conditions. Based on these studies, all of the alternatives to FBS seem to be suitable replacements; however, each has its own advantages and drawbacks. Very few studies have investigated the effects of the supplements on the immunomodulation of ASCs; the transcriptome, proteome and secretome; and the ultimate effects in appropriate animal models. The selection of medium supplementation will depend on the downstream application of the ASCs and their efficacy and safety in preclinical studies.